Marketing Strategy of Property Sector Crowdfunding Company of PT Esa Dana Unggul - Fajar Surya Arianto; Tantri Yanuar Rahmat Syah; Rhian Indradewa; Dimas Angga Negoro (Syntax Idea)
The demand for housing needs in Indonesian society is still quite large and this is positively welcomed by housing developers to compete in providing the best housing for the community. From the data on available housing units above compared to the housing needs (backlog) by the community, there is still a very large gap. For example, the need for houses in West Java in 2021 is 2,638,153 units, while the available housing units in 2021 are only 11,115 units. In fulfilling the provision of residential houses, small and medium scale property developers need capital both for purchasing land and building units. This is where crowdfunding exists to help developers take advantage of opportunities to provide housing by supporting the availability of developer capital. From the investor side, Securities Crowdfunding is also a new alternative as a choice of investment instruments. The increase in the number of people who are aware of investment currently is also accompanied by an increasing number of investment instruments that are growing in society. Through the SCF scheme, investors and parties who need funding will be brought together through a digital-based platform or application. This is where property developers need capital and the desire of investors to look for investment instruments that are safe and with attractive investment profit sharing can be filled with the presence of SCF.Research method using STP and Marketing Mix (NICE and 4 P) strategies.Result This analysis can help the securities crowdfunding companies in property in Indonesia use their marketing strategy.